2015
DOI: 10.1093/gbe/evv081
|View full text |Cite
|
Sign up to set email alerts
|

Transposable Elements and DNA Methylation Create in Embryonic Stem Cells Human-Specific Regulatory Sequences Associated with Distal Enhancers and Noncoding RNAs

Abstract: Despite significant progress in the structural and functional characterization of the human genome, understanding of the mechanisms underlying the genetic basis of human phenotypic uniqueness remains limited. Here, I report that transposable element-derived sequences, most notably LTR7/HERV-H, LTR5_Hs, and L1HS, harbor 99.8% of the candidate human-specific regulatory loci (HSRL) with putative transcription factor-binding sites in the genome of human embryonic stem cells (hESC). A total of 4,094 candidate HSRL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
151
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(159 citation statements)
references
References 64 publications
8
151
0
Order By: Relevance
“…During embryogenesis, transcriptional activities of the common elements LINE1 (long interspersed nuclear elements) and Alu increase markedly for a short period of time following genome-wide demethylation at the 2-cell stage but decrease back to the basal level before genome-wide remethylation and are thought to be maintained at a relatively constant hypermethylated state thereafter in somatic cells (Guo et al 2014; Smith et al 2014). This brief activity early in embryogenesis may lead to the creation of human-specific transcription factor binding sites associated with a pluripotent stem cell phenotype (Glinsky 2015). Therefore, altered DNA methylation during this critical embryonic stage may have broad potential to affect downstream regulatory function in the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…During embryogenesis, transcriptional activities of the common elements LINE1 (long interspersed nuclear elements) and Alu increase markedly for a short period of time following genome-wide demethylation at the 2-cell stage but decrease back to the basal level before genome-wide remethylation and are thought to be maintained at a relatively constant hypermethylated state thereafter in somatic cells (Guo et al 2014; Smith et al 2014). This brief activity early in embryogenesis may lead to the creation of human-specific transcription factor binding sites associated with a pluripotent stem cell phenotype (Glinsky 2015). Therefore, altered DNA methylation during this critical embryonic stage may have broad potential to affect downstream regulatory function in the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, it is reported that partial reprogramming by expression of Oct4, Sox2, Klf4, and c-Myc (OSKM) improve cellular and physiological hallmarks of aging and extends the lifespan of mice with premature aging (Ocampo et al, 2016). It is probable that interactions between pluripotency factors and retrotransposons (Glinsky, 2015) coordinate and execute the epigenetic program that controls individual development.…”
Section: Long Non-coding Rnas In the Epigenetic Regulation By Human Ementioning
confidence: 99%
“…For example, syncytin is a product of the activity of human endogenous viruses W (HERV-W) aids in normal placental development during pregnancy (Mi et al, 2000). Almost all regulatory loci with pluripotency transcription factor-binding sites are located in LTR7/HERV-H, LTR5/HERV-K, and L1HS (human specific) that are distinct from other genomes (Glinsky, 2015). Moreover, ERVs are controlled in embryonic development by the action of TRIM28/KAP1 (Rowe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, they documented that 18% and 31% of total transcription start sites in mouse and human, respectively, are located within retrotransposon sequences [2ofgenetic8] . Beyond protein-coding genes, retrotransposons provide promoters and enhancers for long noncoding RNAs (lncRNAs) [84,[87][88][89] . In addition, a large number of gene enhancers are ʺdonatedʺ by retrotransposons, providing the ability of tissue-and species-specific gene expression [84,90,91] .…”
Section: R E T R O T R a N S P O S O N S : A W E B O F Sophisticatedmentioning
confidence: 99%